The Chromosomes of Zeugodacus tau and Zeugodacus cucurbitae: A Comparative Analysis - Gouvi, G.; Gariou-Papalexiou, A.; Augustinos, Antonios A.; Drosopoulou, E.; Tsiamis, George; Bourtzis, Kostas; Zacharopoulou, A. (Frontiers in Ecology and Evolution, 2022)
Availability of polytene chromosomes and development of polytene chromosome maps have greatly facilitated genetic analysis in Diptera and understanding of chromosomal organization. In tephritids, following the first polytene chromosome maps constructed for the Mediterranean fruit fly, Ceratitis capitata, additional maps have been developed for only few species belonging to the main genera of agricultural importance that are Anastrepha, Bactrocera, Ceratitis, Dacus, Rhagoletis, and Zeugodacus. Comparison of the polytene chromosomes of these species has pointed to the presence of chromosomal rearrangements that can, at least partially, shed light to the chromosomal evolution in this family. Up to now, polytene chromosome maps are available only for one Zeugodacus species, that is Zeugodacus cucurbitae. Here we report the cytogenetic analysis of the mitotic and polytene chromosomes of the pumpkin fly, Zeugodacus tau, along with a comparative analysis with polytene chromosomes of Zeugodacus cucurbitae as well as other tephritids. In situ hybridization experiments resulting to chromosomal localization of selected genes in both species are also presented. The genes used as markers are hsp70, hsp83, scarlet and white pupae. The established homologies presented in this study verify that the two Zeugodacus species are genetically close and support the current taxonomic placement of the Zeugodacus genus. The differences in polytene chromosome level, in combination with results of in situ hybridization experiments, reveal the presence of chromosomal rearrangements, mainly inversions, to both closely and distantly related species, which could potentially be a useful diagnostic tool.